TEORI NASIKH-MANSUKH AL-QUR’AN SEBAGAI PEMBAHARUAN HUKUM ISLAM DALAM PEMIKIRAN ABDULLAHI AHMED AN-NA’IM DAN MUHAMMAD SYAHRUR - Mun’im, Zainul (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
The Qur’an as a source of Islamic law has an important role in theraising of theories of Islamic law as a method of interpretation. Amongthese theories, there is a theory of Nasikh-Mansukh. This theory is oneof the several theories of interpretation that have introduced the classicalIslamic jurists as a legal determination in the Qur’an. Most of thecontemporary Islamic jurists sought to reconstruct the theory in order todevelop Islamic law more relevant to the demands of the times. Amongthem are Abdullahi Ahmed An-Na’im and Muha} mmad Shahrur. An-Na’im theory of Nasikh Mansukh is to elimination Madaniyyah verseswith Makkiyah verses, while Shahrur theory of Nasikh-Mansukh isthe elimination of the previous shari’ah to be replaced by the shari’ahof the Prophet Muhammad. The ir ideas, has different implications tothe Islamic law. implications of An-Na’im’s theory emphasizes genderequality and religious equality before the law, while Shahrur’s theoryhas wider implications than the theory of an-Na’im above. In otherwords, is has implications for the Islamic law that is more responsiveto punishment, family law, marital law, the protection of life (murderpunishment), and so forth.